CD11b Activity Modulates Pathogenesis of Lupus Nephritis - Khan, Samia Q.; Khan, Imran; Gupta, Vineet (Frontiers in Medicine, 2018)
Lupus nephritis (LN) is a common complication of systemic lupus erythematosus (SLE) with unclear etiology and limited treatment options. Immune cell infiltration into the kidneys, a hallmark of LN, triggers tissue damage and proteinuria. CD11b, the α-chain of integrin receptor CD11b/CD18 (also known as αMβ2, Mac-1, and CR3), is highly expressed on the surface of innate immune cells, including macrophages and neutrophils. Genetic variants in the human ITGAM gene, which encodes for CD11b, are strongly associated with susceptibility to SLE, LN, and other complications of SLE. CD11b modulates several key biological functions in innate immune cells, including cell adhesion, migration, and phagocytosis. CD11b also modulates other signaling pathways in these cells, such as the Toll-like receptor signaling pathways, that mediate generation of type I interferons, a key proinflammatory cytokine and circulating biomarker in SLE and LN patients. However, how variants in ITGAM gene contribute to disease pathogenesis has not been completely established. Here, we provide an overview of CD11b modulated mechanisms and the functional consequences of the genetic variants that can drive disease pathogenesis. We also present recent insights from studies after pharmacological activation of CD11b. These studies offer novel mechanisms for development of therapeutics for LN, SLE and other autoimmune diseases.